Morphological Significance in the Historical Narratives of Ali Al-Jarem: Broken Plural Forms as a Model - علي, کشە عبد الله; كريم, هيوا عبد الله (Sulaimani Journal for Humanities, 2019)
In relation to words formation and meanings, semantic and construction aspect of words, there is a significantconnection between morphological and semantic aspects of words and phrases, in a way that in case any alterations occurred, for example increasing or decreasing in formation, there is an inevitable impact in the meaning they represent. In other words, similarly, any word formation in a language is ultimately serving one purpose and one purpose only which is expressing a unique expression and particular meaning of the words that corresponds to the synonymic purpose and meaning of its roots. Based on the aforementioned information, and the important relationship of these two components, this research paper concerns itself with morphological meaning of a particular type of (pluralization)in the historical novels of Ali al-Jarim. The analytical basis of the study will revolve around the significant relationship between the inflectional morphology on the one hand with the thematic and contextual aspect within his literary works, on the other. The basis of the study is to shed light on the archaic pluralization processes within the most predominant and different contextual-related forms of his novels. Later, the roles and the importance of their diversity and the reason for specifying a particular context in relation to a particular formation are analyzed, whereas other formations were deemed neglected, as a result, meanings would be further epitomized. In order to implement the analytical endeavors of this research paper and based on the methodology of analytical processes, the paper comprises of a specific arrangement which is that of an epilogue as well as theoretical and practical analysis. And hence, the most important outcomes of the study are ultimately highlighted and presented. As part of the epilogue, in a precise and thorough manner, two main points are elaborated, first one of which is the concept and the importance of the morphological meanings whereas the second one is distinguishing irregular broken plural in Arabic language and the two main patterns within broken irregular Arabic plural. The first part of the study will concern itself with identifying the two types of broken plural in Arabic language, that’s to say both (plural of multitude- Jami’ al-Qila) and (plural of few- Jami’ al- Kothra). Through analyzing an example or more, their meanings and transliterations are explained. Despite the fact that most plural formations mentioned in the novels are prepared and listed in the inflectional morphology table. However, the second part of the study demonstrates the semantic dimensions of the different and diverse essence of that particular type of plural form known as Arabic broken plural, and later this diversity of usage by the author is further explained through examining the author’s all six novels and identifying the contextual analysis of the parts chosen for this study. In conclusion, the results and the outcome of the research paper are all vividly demonstrated to the reader.